Courts and terrorism : nine nations balance rights and security / edited by Mary L. Volcansek, John F. Stack, Jr. - Volcansek, Mary L., 1948-; Stack, John F. (Cambridge University Press, 2011)
Since ancient times, terror tactics have been used to achieve political ends and likely will continue into the foreseeable future. Preserving national security and the safety of civilian populations while maintaining democratic principles and respecting human rights requires a delicate balancing act. In democracies, monitoring that balance typically falls to the courts. Courts and Terrorism examines how judiciaries in nine separate nations have responded, not just to the current wave of Al Qaeda threats, but also to narco-trafficking, domestic terrorism and organized crime syndicates. Terrorism is not a new phenomenon, and even though the reactions have varied significantly, common themes emerge. This volume discusses eleven case studies and analyzes the experiences of these various nations in their battles with terrorism to reveal the judicial quandary for democratic governance and the rule of law in the twenty-first century.